Sophomore's Leaf

Calculus Level 5

It is a fairly well-known property that x x d x \displaystyle \int x^x \; \mathrm{d}x is impossible to evaluate using standard mathematical functions.

Let f ( x ) = x x f(x)=|x|^x and g ( x ) = ( x ) x g(x) = (-x)^{-x} .
Let A A be the area of the region bounded by f f and g g .

Determine 1 0 5 A \big\lfloor 10^5 A \big\rfloor .


The answer is 50785.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Guilherme Niedu
Nov 11, 2017

We can make x = x x = -x and take the positive side, for simplicty. The intersection points will be 0 0 and 1 1 and, since x x is positive, x = x |x| = x . Thus, this becomes:

A = 0 1 ( x x x x ) d x \large \displaystyle A = \int_0^1 (x^{-x} - x^x) dx

A = 0 1 e x ln ( x ) d x 0 1 e x ln ( x ) d x \large \displaystyle A = \int_0^1 e^{-x \ln(x)}dx - \int_0^1 e^{x \ln(x)}dx

A = 0 1 k = 0 1 k ! [ x ln ( x ) ] k d x 0 1 k = 0 1 k ! [ x ln ( x ) ] k d x \large \displaystyle A = \int_0^1 \sum_{k=0}^{\infty} \frac{1}{k!} [-x \ln(x)]^k dx - \int_0^1 \sum_{k=0}^{\infty} \frac{1}{k!} [x \ln(x)]^k dx

A = k = 0 1 k ! [ 0 1 [ x ln ( x ) ] k d x 0 1 [ x ln ( x ) ] k d x ] \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1}{k!} \left [ \int_0^1 [-x \ln(x)]^k dx - \int_0^1 [x \ln(x)]^k dx \right ]

Make u = ln ( x ) u = -\ln(x) on both integrals. Then, x = e u x = e^{-u} and d x = e u d u dx = -e^{-u} du :

A = k = 0 1 k ! [ 0 e u ( k + 1 ) u k d u ( 1 ) k 0 e u ( k + 1 ) u k d u ] \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1}{k!} \left [ \int_0^{\infty} e^{-u(k+1)} u^k du - (-1)^k \int_0^{\infty} e^{-u(k+1)} u^k du \right ]

A = k = 0 1 ( 1 ) k k ! [ 0 e u ( k + 1 ) u k d u ] \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1 - (-1)^k}{k!} \left [ \int_0^{\infty} e^{-u(k+1)} u^k du \right ]

Multuply above and below by ( k + 1 ) k (k+1)^k :

A = k = 0 1 ( 1 ) k k ! ( k + 1 ) k [ 0 e u ( k + 1 ) [ u ( k + 1 ) ] k d u ] \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1 - (-1)^k}{k! (k+1)^k} \left [ \int_0^{\infty} e^{-u(k+1)} [u(k+1)]^k du \right ]

Make t = u ( k + 1 ) t = u(k+1) . Then, d t = d u ( k + 1 ) dt = du (k+1) :

A = k = 0 1 ( 1 ) k k ! ( k + 1 ) k 1 k + 1 [ 0 e t t k d t ] \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1 - (-1)^k}{k! (k+1)^k} \cdot \frac{1}{k+1} \left [ \int_0^{\infty} e^{-t} t^k dt \right ]

The integral is the exact definiton of Γ ( k + 1 ) \Gamma(k+1) , which is equal to k ! k! :

A = k = 0 1 ( 1 ) k k ! ( k + 1 ) k + 1 k ! \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1 - (-1)^k}{k! (k+1)^{k+1}} \cdot k!

A = k = 0 1 ( 1 ) k ( k + 1 ) k + 1 \large \displaystyle A = \sum_{k=0}^{\infty} \frac{1 - (-1)^k}{(k+1)^{k+1}}

Make n = k + 1 n = k+1 :

A = n = 1 1 ( 1 ) n 1 n n \large \displaystyle A = \sum_{n=1}^{\infty} \frac{1 - (-1)^{n-1}}{n^n}

The numerator will be 0 0 for odd n n and 2 2 for even n n . Thus:

A = n = 1 2 ( 2 n ) 2 n \large \displaystyle A = \sum_{n=1}^{\infty} \frac{2}{(2n)^{2n}}

This sum quickly converges ( 5 5 steps) to:

A = 0.507855486 \color{#20A900} \boxed{ \large \displaystyle A = 0.507855486}

Correct to 9 9 decimal places. Thus:

A = 50785 \color{#3D99F6} \boxed{ \large \displaystyle \lfloor A \rfloor = 50785}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...